Manfaat Penerapan Standar pada Perusahaan Tuna di DKI Jakarta - Linthin, Retno Dwiputri; Zakaria, Fransiska R; Trilaksani, Wini (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
Tuna is one of the most valuable fishery commodities produced in Indonesia. In a great measure of tuna production in Indonesia is exported to several destination countries such as Japan, the European Union and America. The demand for tuna in Japan and the United States from year to year has never decreased. Furthermore, the role of tuna industry from time to time is increasingly important and strategic, especially in sustaining the nation's economy as tuna plays an important role in many people’s health in which Tuna provides high quality protein. In terms of sustainable tuna consumption, valuable creative activities (VCA) is required to be formulated, so all resources (tangible, intangible, human resources) are able to produce prime fishery products that have high quality standard and high value content, competent, safe, traceable, both nationally and internationally. The Prime fishery products are able to be produced if the fishery industry successfully applies several standards both national and international such as ISO, SNI, CODEX, and standards from importers. In terms of applying those standards, it is worth reviewing few of benefits of standard implementation. Associated with the standards applied by the company, there are studies of the benefits of standard implementation in tuna industry in Muara Baru, DKI Jakarta. The purpose of this study was to assess the benefits of standard implementation in tuna companies. The method used was descriptive and it uses several tests including profitability ratio analysis (net profit margin, return on asset, return on equity, profit margin). The results of this study are that both companies had implemented the standard well, standard understanding by both companies still exist different, while from the financial sector the company was able to increase profits